PENGARUH PARTISIPASI ANGGARAN, PERSEPSI KEADILAN DISTRIBUTIF DAN KEADILAN PROSEDURAL TERHADAP KINERJA MANAJEMEN HOTEL - Wiryanata, I Gusti Ngurah Agung; Sudarsana, Ketut; Oka Geria, Anak Agung Gede (Pusat penelitian & Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2011)
Budgeting is one of the defining factors in the success of hotel industry. It can be a tool for coordination, delegation and monitoring which is beneficial for managers to improve their performance. This study aims to investigate the impact of participation, perception of distributive justice, and perception of procedural justice towards management performance. Data were collected from star hotels in Badung Regency based on the hotel list published by Bali Government Office in 2009. The analyses shows that there is no significant impact of participation in budgeting on management performance, meanwhile the perception of distributie justice and procedural justice significantly influence management performance.